The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2147/opth.s56735
|View full text |Cite
|
Sign up to set email alerts
|

Bimatoprost/timolol fixed combination versus latanoprost in treatment-naïve glaucoma patients at high risk of progression: a pilot study

Abstract: ObjectiveTo compare a fixed combination of 0.03% bimatoprost and 0.5% timolol (BTFC) with latanoprost monotherapy (LM) in treatment-naïve patients with open-angle glaucoma (OAG) and risk factors for glaucomatous progression.MethodsPatients were enrolled at 15 sites in Spain and Portugal, and were randomized 1:1 to BTFC or LM. Patients instilled one drop of medication once per day at 8 pm for 12 weeks. The primary outcome was change in intraocular pressure (IOP) at 12 weeks.ResultsOf 81 patients enrolled, 43 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Several clinical studies conducted in European countries have reported the superior efficacy of BTFC compared with bimatoprost monotherapy 25 , 33 – 35 or latanoprost monotherapy. 32 , 36 There has been no comparative study conducted in the People’s Republic of China on the efficacy of BTFCs against PGA monotherapies to date.…”
Section: Efficacy Studies Of Bimatoprost and Btfc Including Comparatmentioning
confidence: 99%
“…Several clinical studies conducted in European countries have reported the superior efficacy of BTFC compared with bimatoprost monotherapy 25 , 33 – 35 or latanoprost monotherapy. 32 , 36 There has been no comparative study conducted in the People’s Republic of China on the efficacy of BTFCs against PGA monotherapies to date.…”
Section: Efficacy Studies Of Bimatoprost and Btfc Including Comparatmentioning
confidence: 99%